Indonesia’s Village Fiscal Transfers: A Fiscal Decentralisation Review - Khairullah Anshari (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2017)
This study intends to discuss the empirical aftermath of Indonesia’s first policy implementation of the Village Law 2014 the village fiscal transfers: the new village fund (Dana Desa) from the state with the prior fiscal transfers from the regency for the villages, focussing on allocation and expenditure action in Banjar Regency, South Kalimantan Province. The study findings show that the village fiscal transfers are dominantly allocated equally/same amount for every village and some allocated proportionally depend on the weight of village variables. Despite resulting inequality in allocation, the main considerations of the alloca- tion method are to have village fiscal sufficiency and maintain state-regency- villages relation. The high increase of expenditures is mostly in infrastructure development and remuneration for village officials. In spending, the village gov- ernment has to improve the accountability especially the punctuality of upward accountability and starts to initiate the downward accountability. Overlapping authorities between regency and village, and limitations in human resources should be solved immediately to smooth the process of decentralisation to villages.